Role of Technology and its Impact on Criminal Policy - Sabah Abdul Kareem, Researcher. Ahmed; Hamza Asel, Prof. Dr. Ali (Basra studies journal, 2024)
To introduce the technological role and its impact on criminal policy the study must mention or follow the historical path of the nature of this development and the extent of its impact on branches of law in general, and the extent of the need for this technology in the various details of life and what protection is provided for it. Therefore, The legislator must quickly criminalize these new acts and set deterrent penalties for them, and countries are also required to think about reconsidering their criminal policies related to this technological progress, this can be achieved by finding plans and methods respond to the development of crime in accordance with the technological progress. Rather, these countries are preparing their advanced criminal strategy by finding new ways to deal with each other within the framework of tracking criminals and prosecuting them wherever they go. And to unify a new framework for fruitful cooperation in this field, especially since the traditional mechanisms of international cooperation have become beyond the complexity of procedures and slow implement.